Ask Your Question

Revision history [back]

click to hide/show revision 1
initial version

solve function output function of variable for which to solve

Here is an example:

solve(3*z^2/(2-12*z^2+sqrt(1 - 12*z^2)) == u, z)

Output is:

[z == -sqrt(1/3)*sqrt((sqrt(-12*z^2 + 1)*u + 2*u)/(4*u + 1)), z == sqrt(1/3)*sqrt((sqrt(-12*z^2 + 1)*u + 2*u)/(4*u + 1))]

As you can see, the solution is a function of both u and z. Surely this is a bug? Otherwise, if I am doing something incorrectly, can someone please let me know what has gone wrong.

Thank you in advance!